Synchronization of the Cardiac Pacemaker Model with Delayed Pulse-coupling - Akhmet, M. (Discontinuity, Nonlinearity, and Complexity, 2026)
We reconsider the C. Peskin model of the cardiac pacemaker assuming that pulse-couplings are delayed. Sufficient conditions for synchronization of identical and non-identical oscillators are obtained. The results are demon- strated with numerical simulations.